1984
DOI: 10.1002/j.1460-2075.1984.tb02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Covalently closed circles of human adenovirus DNA are infectious.

Abstract: Replication of the linear adenovirus DNA molecule is thought to result from semiconservative synthesis off linear templates, starting from origins at either end of the genome. Recently, however, it has been shown that in cells infected with adenovirus type 5 (Ad5) a significant fraction of the ends of viral DNA molecules become joined head‐to‐tail due at least in part to the formation of covalently closed circles. Circular DNA is not present in virions but joining of the ends of viral DNA is detectable shortly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 33 publications
1
72
0
Order By: Relevance
“…Once established, however, these insertion mutants seemed to be quite stable: when a mutant with an insertion of 1.7 kb was passaged five times successively in 293 cells and replaqued, 24 out of 24 plaque isolates analyzed had a structure which was identical to that of the parental mutant (unpublished observations). In other studies we have succeeded in constructing a stable insertion mutant, Ad5in52, with 2.2 kb of inserted DNA (Graham, 1984) but we are not aware of any larger insertions which have been introduced into the AdS genome in the absence of compensatory deletions. Viral and plasmid cloning vectors with deletions of viral DNA To increase the cloning capacity of AdS and thereby extend its utility as a vector, we developed a mutant with extensive deletions in early region 1 (El) and E3 (Haj-Ahmad and .…”
Section: Rescue Of Eia Insertion Mutantsmentioning
confidence: 99%
“…Once established, however, these insertion mutants seemed to be quite stable: when a mutant with an insertion of 1.7 kb was passaged five times successively in 293 cells and replaqued, 24 out of 24 plaque isolates analyzed had a structure which was identical to that of the parental mutant (unpublished observations). In other studies we have succeeded in constructing a stable insertion mutant, Ad5in52, with 2.2 kb of inserted DNA (Graham, 1984) but we are not aware of any larger insertions which have been introduced into the AdS genome in the absence of compensatory deletions. Viral and plasmid cloning vectors with deletions of viral DNA To increase the cloning capacity of AdS and thereby extend its utility as a vector, we developed a mutant with extensive deletions in early region 1 (El) and E3 (Haj-Ahmad and .…”
Section: Rescue Of Eia Insertion Mutantsmentioning
confidence: 99%
“…The absence of the adenovirus packaging signal from this helper genome completely prevents its packaging into infectious virus particles. The conception of this system was derived from three observations: (1) recombinant baculovirus based on the genome of Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) can efficiently transduce certain mammalian cells in tissue culture; [27][28][29] (2) when properly joined, adenovirus ITRs can be efficiently utilized as an adenoviral origin of replication; 30,31 and (3) Cre recombinase can efficiently excise and circularize a DNA fragment flanked by two loxP sites. 32,33 Previous studies demonstrated that AcMNPV is capable of transducing mammalian cells without virus gene expression or replication.…”
Section: Introductionmentioning
confidence: 99%
“…40 This method was developed based on the construction of an Ad genomic plasmid by inserting pBR322 into the XbaI site in the E1 region of a circularized wt Ad genome isolated from the Ad-infected cell lysate. 41,42 This plasmid, known as pJM17, is too big to be encapsidated because of the insertion of the pBR plasmid sequence. Therefore, it can be used to cotransfect 293 cells with a smaller plasmid (shuttle vector) that contains the left-end arm of the Ad genome (0 -16 mu) with its E1 region substituted by the expression cassette of the transgene.…”
Section: Three Basic Methods For Generating Radsmentioning
confidence: 99%